Malabbiri: Studi Mahasiswa di Fakultas Ilmu Sosial dan Hukum Universitas Negeri Makassar - Salsabilah, Adeliya Natasha; Ima Kesuma, Andi; Junaeda, St. (Rayhan Intermedia, 2024)
This research aims to find out the view of Makassar women, the view of Malabbiri and the elements that influence the view of Malabbiri. This research uses descriptive qualitative research. The key informants in this research are students of the Faculty of Social Sciences and Law as the main subject of research. Researchers used data collection techniques conducted by observation, interview, and documentation. The results showed that Makassar women are women who are brave, loyal and always maintain the value of siri'na pacce in behavior and behavior, and are able to serve their husbands well, because that is the provision in serving their husbands well. Malabbiri is a woman who maintains attitude and behavior, is intellectually intelligent, maintains polite and courteous ethics, is elegant in dress and speech. The element that influences the view of Malabbiri is modernity, including the entry of outside cultures, technological developments, and environmental influences. Translated with DeepL.com (free version)